Modifying aluminum phthalocyanine with quantum dots to promote cellular uptake and enhance the efficacy of anticancer photodynamic therapy - Lei, Li; Dai, Bin; Han, Ting; Zhou, Cheng; Gong, Zhao; Zhang, Ping (Frontiers in Materials, 2022)
Photodynamic therapy (PDT) is regarded as an alternative antitumor therapy which involves the administration of photosensitizers (PSs) and the irradiation with specific light. However, conventional PDT therapy has been limited to the efficiency of PSs delivery. Nanocarrier system could provide an effective platform for PSs delivery and improve the efficiency of antitumor PDT therapy. In this article, we prepared the complex consisting of aluminium phthalocyanine (AlPcS) and CdSe/CdZnS core-shell structure QDs and investigated the interaction between the complex and tumor cells. The more significant internalization of the conjugation was observed compared to the free AlPcS via confocal fluorescence imaging. The tumor cells exhibited obvious apoptotic trend after QDs-AlPcS-mediated PDT.